Health Education and Cooking Demonstration of Skipjack Tuna Nuggets as a Healthy Snack Alternative for Hypertension Prevention in Boneoge Village - Ahmil, Ahmil; Matasa, Fitria Wahyu Ningrum; Ziadah, Maydinar; Maila, Jingga Fitria; Misna; Novia; Mayumi; Mutiara; Ni Wayan Ulantari; Sakina (Edumedia Solution, 2026)
Hypertension is a public health problem whose prevalence continues to increase worldwide. According to the World Health Organization (WHO, 2023), more than 1.28 billion adults are living with hypertension, with the majority residing in developing countries. In Boneoge Village, the community still tends to consume foods high in salt and fat, while the potential of local food sources such as skipjack tuna has not been fully utilized. In fact, skipjack tuna is rich in protein, omega-3 fatty acids, and various micronutrients that play an important role in maintaining cardiovascular health. This community service activity aimed to increase residents’ knowledge about hypertension, train their skills in processing skipjack tuna into nuggets as a healthy snack alternative, and support hypertension prevention efforts through the use of local food resources. The program was carried out through health education and a live cooking demonstration, involving 15 participants from RT 10 Boneoge on August 19, 2025. The results showed an improvement in knowledge regarding healthy eating patterns as well as practical skills in processing tuna nuggets. Thus, this program proved effective in raising awareness, developing community skills, and encouraging the optimization of local food in preventing hypertension.